Tauhid Emansipatoris dan Tazkiyatun Nafs Transformatif sebagai paradigma teologis pembebasan: Rekonstruksi konseptual masyarakat tanpa kemiskinan - Lum’atul Andalusiah; Elvita Kharimatul Aulia; Baiti Nur Zahila; Ali Hasan Siswanto (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
Poverty remains a multidimensional problem that persists amid global economic development and social modernization. Conventional development approaches oriented toward economic growth have proven insufficient to address the structural and cultural roots of poverty. In this context, poverty studies within Islamic scholarship are still predominantly dominated by normative and economic perspectives, while the spiritual-transformative dimension based on theology and Sufism has not been conceptually developed as a paradigm for social change. This research gap indicates the need for a theoretical reconstruction that integrates Islamic spirituality with social transformation toward a poverty free society. This article employs the theoretical approach of Transformative Tazkiyatun Nafs based on Emancipatory Tauhid, which positions self-purification as the foundation for social change and liberation from poverty structures. The study uses a qualitative conceptual method through library research, applying critical-constructive analysis of Islamic theological literature, social Sufism, and theories of social change. The main argument of this article asserts that poverty is not merely an economic issue, but also a spiritual, moral, and structural crisis. Therefore, transformation toward a poverty-free society must begin with the transformation of tauhid consciousness, which fosters social solidarity, distributive justice, and community-based economic empowerment. The transformative tazkiyatun nafs approach offers an integrative model that links individual transformation with social transformation as a strategy for creating a poverty free society. The scientific contribution of this study lies in developing a new paradigm of emancipatory tauhid, integrating Sufism with social change theory, and constructing a conceptual framework for a poverty-free society based on transformative theology, thereby enriching contemporary Islamic Studies